Natural dog care - Fogle, Bruce (Dorling Kindersley LondonGB, 1999)
Promotes natural approaches to all aspects of the care of dogs. Addresses their physical, mental, social and emotional development and needs. Presents training techniques, including obedience training, and emphasises the importance of creating an owner/companion relationship that is mutually beneficial. Discusses numerous health disorders including: skin disorders, othhopaedic problems, and ailments affecting the cardiovascular, endocrine, gastrointestinal, reproductive, respiratory, urinary and central nervous systems. Explores the benefits and disadvantages of both conventional and complementary veterinary medicine and promotes both approaches for preserving good canine health and treating illnesses.